Type III Secretion 1 Effector Gene Diversity Among Vibrio Isolates From Coastal Areas in China - Wu, Chao; Zhao, Zhe; Liu, Yupeng; Zhu, Xinyuan; Liu, Min; Luo, Peng; Shi, Yan (Frontiers in Cellular and Infection Microbiology, 2020)
Vibrios, which include more than 120 valid species, are an abundant and diverse group of bacteria in marine and estuarine environments. Some of these bacteria have been recognized as pathogens of both marine animals and humans, and therefore, their virulence mechanisms have attracted increasing attention. The type III secretion system (T3SS) is an important virulence determinant in many gram-negative bacteria, in which this system directly translocates variable effectors into the host cytosol for the manipulation of the cellular responses. In this study, the distribution of the T3SS gene cluster was first examined in 110 Vibrio strains of 26 different species, including 98 strains isolated from coastal areas in China. Several T3SS1 genes, but not T3SS2 genes (T3SS2α and T3SS2β), were universally detected in all the strains of four species, Vibrio parahaemolyticus, Vibrio alginolyticus, Vibrio harveyi and Vibrio campbellii. The effector coding regions within the T3SS1 gene clusters from the T3SS1-positive strains were further analyzed, revealing that variations in the effectors of Vibrio T3SS1 were observed among the four Vibrio species, even between different strains in V. harveyi, according to their genetic organization. Importantly, Afp17, a potential novel effector that may exert a similar function as the known effector VopS in T3SS1-induced cell death, based on cytotoxicity assay results, was found in the effector coding region of the T3SS1 in some V. harveyi and V. campbellii strains. Finally, it was revealed that differences in T3SS1-mediated cytotoxicity were dependent not only on the variations in the effectors of Vibrio T3SS1 but also on the initial adhesion ability to host cells, which is another prerequisite condition. Altogether, our results contribute to the clarification of the diversity of T3SS1 effectors and a better understanding of the differences in cytotoxicity among Vibrio species.